First data on habitat preference, diet and length-weight relationship of Gobius incognitus Kovačić & Šanda, 2016 (Pisces: Gobiidae) - Tiralongo, Francesco (Array, 2020)
In this work, we present first data on biological and ecological aspects of Gobius incognitus from specimens from the Ionian Sea (central Mediterranean Sea). In particular, we provided first data on habitat preference, diet and length-weight relationship of G. incognitus on material with confirmed species identity. The species preferred “mixed bottom” (sand and rocks), where it reached relatively high abundances. The diet analysis showed that G. incognitus is a generalist and opportunistic feeder. However, small benthic crustaceans were the most important prey group. The mean total length of specimens was 6.72 ± 1.85 cm and the growth was positive allometric.